Case Report: Successful management of psychogenic non-epileptic seizures with intranasal esketamine - Hashmi, Muneeb; Mugunthan, Padmasini; Jain, Priyal; Nimmakayala, Tharun; Alnaher, Sarah (Frontiers in Psychiatry, 2025)
IntroductionPsychogenic non-epileptic seizures (PNES), or functional seizures (FS), are episodes that resemble epileptic seizures but may be psychological in origin. Unlike epileptic seizures, which are linked to abnormal electrical activity in the brain, functional seizures may be associated with psychological and/or physical distress, and do not show the same electrical patterns on an electroencephalogram (EEG). Esketamine, a derivative of the anesthetic ketamine, is approved by the U.S. Food and Drug Administration (FDA) for treatment-resistant depression (TRD) and major depressive disorder (MDD) with suicidal thoughts or actions.Methods/ResultsThis report discusses a patient with TRD and PNES, where the administration of esketamine effectively resolved both conditions.DiscussionIt explores the potential therapeutic effects of esketamine on PNES, in addition to its antidepressant properties.